Hans Scharoun, 1893-1972 : outsider of modernism - Syring, Eberhard, 1951-; Kirschenmann, Jörg C. (Köln ; Los Angeles : Taschen, 2004)
This text studies the architecture of Hans Scharoun. It provides an analysis of his career until his death in 1972.
Includes bibliographical references (page 96).
ARC
Department of architecture
Keywords: Scharoun, Hans, -- 1893-1972; Scharoun, Hans, -- 1893-1972 -- Criticism and interpretation; Criticism, interpretation, etc